Rancang Bangun Aplikasi Pelaporan Bencana Di Badan Penanggulangan Bencana Daerah (Bpbd) Kabupaten Gunung Mas Berbasis Website - Yosepha, Elsa; Widiatry, Widiatry; Pranatawijaya, Viktor Handrianus (Universitas Palangka Raya, 2023)
Regional Disaster Management Authority (RDMA) is a government institution that is authorized in terms of dealing with disasters in the regions, both provinces and districts/cities by referring to the policies set by National Disaster Management Authority (NDMA). The vision of RDMA is to create a prosperous, safe, and comfortable Gunung Mas Regency through responsive, fast and appropriate disaster management. Therefore, The Design of Website Based Disaster Reporting App in Regional Disaster Management Authority (RDMA), which aims to provide information to the public about the RDMA of Gunung Mas Regency and as a forum for distributing Disaster Reports that occur in the Gunung Mas regency.The methodology used in making this website is waterfall, with stages, namely the Requirements Definition stage is described using a flowchart, Requirements Analysis and Definition is described through DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), and database. Implementation and Unit Testing with the programming languages ​​used are HTML, PHP, CSS, Bootstrap, Javascript, and MySQL, Integration and System Testing using the Black Box Method. The features contained in this website are Home, RDMA Profile, News, Gallery Information, Knowledge about Disasters, Disaster Reporting Services related to reporting procedures and report forms. With the aim that people can get information about RDMA in Gunung Mas regency quickly and people in Gunung Mas regency have a place to submit Disaster Reports that occur in the Gunung Mas regency area